2018
DOI: 10.3329/nimcj.v9i2.38913
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Respiratory Diseases among Admitted Children in Pediatric Pulmonology Unit : A Tertiary Center Experiences

Abstract: Background :_The spectrum of respiratory illness is wide and includes diseases of upper and lower airways, communicable and non-communicable types. The variation in pattern of morbidity mortality of respiratory illness may be affected by different environmental and climatic variation in different parts of the world.Objective : The present study intended to explore the pattern of respiratory illnesses seen in Bangladeshi children admitted with respiratory illnesses.Methods :_The present prospective observationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…The cause was unknown, it might be decreased practice of breast feeding the major predisposing factor for respiratory illness. In this study majority of Pneumonia and Bronchiolitis were found during autumn and late Autumn whereas asthma were common in late autumn and winter, similar to the results found in in the study of Begum et al 14 .…”
Section: Figure Ii: Seasonal Variation Of Respiratory Illness Among Ssupporting
confidence: 92%
“…The cause was unknown, it might be decreased practice of breast feeding the major predisposing factor for respiratory illness. In this study majority of Pneumonia and Bronchiolitis were found during autumn and late Autumn whereas asthma were common in late autumn and winter, similar to the results found in in the study of Begum et al 14 .…”
Section: Figure Ii: Seasonal Variation Of Respiratory Illness Among Ssupporting
confidence: 92%
“…There is a close association among unhealthy children to a weakened future of the world [2]. Respiratory infections are a L foremost cause of morbidity and mortality in children under five years of age globally [3,4,5,6]. Approximately, 6.6 million children less than 5 years of age die each year in the world; 95% of them are in low-income countries [7] and one third of the total deaths is due to LRTI [8].…”
Section: Introductionmentioning
confidence: 99%
“…Mungala VK et al also reported bronchopneumonia as the commonest LRTI in their study. In another study by Begum, J et al, (2018) in developing countries Bronchiolitis and Bronchopneumonia are the major contributing respiratory illness. The seasonal variation of the disease varies from season to season and area to area.…”
mentioning
confidence: 97%